An integrative taxonomic review of the agamid genus Bronchocela (Kuhl, 1820) from Peninsular Malaysia with descriptions of new montane and insular endemics - Grismer, L. Lee; Wood, P. L. Jr.; Lee, Cheol Haeng; Quah, Evan S. H.; Anuar, Shahrul; Ngadi, Ehwan; Sites, Jack W. Jr. (Zootaxa, 2015)
An integrative taxonomic analysis is used to identify and describe two new species of the agamid genus Bronchocela (Kuhl) from Peninsular Malaysia: an upland species B. shenlong sp. nov. from Bukit Larut, Perak in the Bintang Mountain Range and Parit Falls, Cameron Highlands, Pahang in the Titiwangsa Mountain Range and an insular species, B. rayaensis sp. nov., from Pulau Langkawi, Kedah off the northwest coast on the border with Thailand. Both species are diagnosed from each other and all other species of Bronchocela on the basis of body shape, scale morphology, and color pattern. The analysis also demonstrates the remarkable genetic similarity of B. cristatella (Kuhl) throughout 1120 km of its range from northern Peninsular Malaysia to western Borneo despite its highly variable coloration and pattern. The two new species are appended to a rapidly growing list of newly described lizard species (60 to date) from Peninsular Malaysia tallied within the last decade.